FPGA as a part of MS WINDOWS control environment - Kołek, Krzysztof; Turnau, Andrzej (My University, 2007)
The attention is focused on the Windows operating system (OS) used as a control and measurement environment. WlNDOWS OS due to extensions becomes a real-time OS (RTOS). Benefits and drawbacks of typical software extensions are compared. As far as hardware solutions are concerned the field programmable gate arrays FPGA technology is proposed to ensure fast time-critical operations. FPGA-based parallel execution and hardware implementation of the data processing algorithms significantly outperform the classical microprocessor operating modes. Suitability of the RTOS for a particular application and FPGA hardware maintenance is studied.

Uwagę skupiono na WlNDOWS - systemie operacyjnym (OS) użytym jako środowisko pomiarów i sterowania. WlNDOWS OS, dzięki rozszerzeniom, staje się systemem operacyjnym czasu rzeczywistego (RTOS). Porównano wady i zalety typowych programowych rozszerzeń. W przypadku sprzętowych rozwiązań, proponuje się użycie technologii FPGA, by wykonać szybkie, krytyczne czasowo operacje. Równolegle wykonanie algorytmu oparte na technologii FPGA i sprzętowa implementacja algorytmów przetwarzania danych w sposób znaczący przewyższają klasyczne mikroprocesorowe tryby pracy. Badane są: dostosowanie oraz użyteczność RTOS dla wybranych aplikacji i rozwiązania sprzętowe wykorzystujące technologię FPGA.
FPGA jako część środowiska sterowania MS Windows
Computer Science
Keywords: MS Windows extensions; soft real time operating system; rozszerzenie MS Windows; miękkie systemy operacyjne czasu rzeczywistego; FPGA-based controller; sterowniki oparte na technologii FPGA